Measuring Chronic Poverty - Foster, James Eric (2012)
A new class of chronic poverty measures is constructed that builds upon Jalan and Ravallion (1998) but does not require resources in different periods to be perfect substitutes when identifying the chronically poor. We use a general mean to combine the resources of a person into a permanent income standard that is then compared to a poverty line to determine when a person is chronically poor. The parameter Beta of the general mean allows for varying degrees of substitutability over time, from perfect substitutes when Beta equals 1 to perfect complements as Beta tends to minus infinity. The decomposable Clark, Hemming and Ulph (1981) poverty measure with the same parameter Beta is applied to the distribution of permanent income standards to measure overall chronic poverty. Each measure has a convenient expression in terms of a censored matrix and satisfies a host of properties including decomposability. We provide an empirical application of the new measures using panel data from urban areas in Argentina.